Seasonal and long‐term changes in elemental concentrations and ratios of marine particulate organic matter. Issue 11 (18th November 2016) - Talarmin, Agathe; Lomas, Michael W.; Bozec, Yann; Savoye, Nicolas; Frigstad, Helene; Karl, David M.; Martiny, Adam C.
Abstract: What is the temporal variability of the elemental stoichiometry of marine microbial communities across ocean regions? To answer this question, we present an analysis of environmental conditions, particulate organic carbon, nitrogen, and phosphorus concentrations and their ratios across 20 time series (3–25 years duration) representing estuarine, coastal, and open ocean environments. The majority of stations showed significant seasonal oscillations in particulate organic elemental concentrations and ratios. However, shorter‐term changes contributed most to overall variance in particulate organic matter concentrations and ratios. We found a correlation between the seasonal oscillations of environmental conditions and elemental ratios at many coastal but not open ocean and estuarine stations. C:N peaked near the seasonal temperature minimum and nutrient maximum, but some stations showed other seasonal links. C:N ratios declined with time over the respective observation periods at all open ocean and estuarine stations as well as at five coastal station but increased at the nine other coastal stations. C:P (but not N:P) declined slightly at Bermuda Atlantic Time‐series Study but showed large significant increases at Hawaii Ocean Time‐series and Arendal stations. The relationships between long‐term changes in environmental conditions and particulate organic matter concentrations or ratios were ambiguous, but interactions between changes in temperature and nutrient availability were important. Overall, our analysis demonstrates significant changes in elemental ratios at long‐term and seasonal time scales across regions, but the underlying mechanisms are currently unclear. Thus, we need to better understand the detailed mechanisms driving the elemental composition of marine microbial ecosystems in order to predict how oceans will respond to environmental changes. Key Points: The elemental composition of marine particulate matter is temporally dynamic Marine regions display unique temporal trends in particulate elemental concentrations and ratios A simple temperature and nutrient limitation model only partially explains temporal changes